1988
DOI: 10.1017/s0022215100107443
|View full text |Cite
|
Sign up to set email alerts
|

Study of the nasopharynx in man by scanning electron microscopy

Abstract: To date only few and often disagreeing studies about human nasopharynx are available. The present research has the purpose to give a contribution to the knowledge of nasopharyngeal epithelium using S.E.M. The study was carried out on biopsies taken from 20 healthy volunteers. The surface of nasopharynx is covered by ciliated cells, microvilli provided cells and goblet cells. Areas covered with squamous epithelium and presumably transitional epithelium were observed. The possibility that ciliated cells become m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…Therefore, two different cellular types can apparently be detected since the very early stages of the considered period. This finding is in opposition to previous researches [26,39] in which the presence of a single cellular type, in different functional stages, was postulated. At the 12th week, specialization appears completed, though, of course, the evolution is continuous and lacks precise boundaries.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, two different cellular types can apparently be detected since the very early stages of the considered period. This finding is in opposition to previous researches [26,39] in which the presence of a single cellular type, in different functional stages, was postulated. At the 12th week, specialization appears completed, though, of course, the evolution is continuous and lacks precise boundaries.…”
Section: Discussioncontrasting
confidence: 99%
“…Only after the 17th week can they be found in the nasopharyngeal roof. Finally, squamous or transitional epithelia have not been observed, but this must not be taken as conclusive since these kinds of epithelia occasionally appear on the lateral walls, preferring the posterosuperior wall [3,26,35]. which is particularly subject to lesions, given the lowering of the posterior arch which exposes it to trauma, even during fetal deglutition [4.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning squamous cell carcinoma, a peculiar morphological aspect of the epithelium seems to be the appearance (extremely variable in shape) of large-sized cells, frequently exfoliated. It must be noted that the network of microplicae (Nettersheim etal., 1981;Zampi and Bianchi, 1989) characterizing the cell apices in such metaplastic areas, is similar to that described in the surface cells of squamous cell carcinoma (Gulisano et al, 1988). The latter is, nevertheless, differentiated, being arranged irregularly and sometimes fragmented.…”
Section: Discussionsupporting
confidence: 65%
“…There have been different approaches to the study of the nasopharyngeal epithelium both from the point of view of the morpho-functional interpretation of normal patterns (Ali, 1965;Bottazzi Bacchi, 1973;Gulisano et al, 1988) and that of potential pathogenic agents (Henderson et al, 1976;Torjussen et al, 1979;Boysen and Reith, 1982a, b;Petruson et al, 1984;Wilhelmsson et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, during chronic flogosis, the number of microvilli-bearing cells increases until they completely substitute for the ciliated cells (Gulisano et al 1987). Such an observation suggested that at least some microvilli-bearing cells are ciliated cells that had lost their cilia, thus exposing the underlying apical microvilli (Gulisano et al 1988). Such a change appears to be the first step in a metaplastic process, during which the epithelium initially becomes pluristratified cuboidal, devoid of ciliated cells, and eventually becoming squamous (Boysen and Reith 1982a, b).…”
Section: Introductionmentioning
confidence: 99%